Computer knowledge required of librarians and information professionals by selected Philippine corporations - Rosales, Prudencio P., Jr (Institute of Library Science, University of the Philippines Diliman, 1999)
Brought by the tremendous impact of computers on the corporate world and on information professions, employers nowadays prefer to hire jobseekers who are computer competent. This alarming trend has great effects to the LIPs because they are basically responsible for handling and processing information. In this connection, it is significant to know the computer knowledge requirement set by the employers of the corporate world.